Meta-Analysis: Effects of Night Shift Work on Hypertension and Sleep Patterns in Factory Workers - Amanda Kesli Ramadhani; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, 2022)
Background: Night shift work has an impact on the health of factory workers. One of the impacts of night shift work is the risk of hypertension and disturbed sleep patterns. The purpose of this study was to determine how big the effect of night shift work on hypertension and sleep patterns in factory workers.Subjects and Method: This was a meta-analysis and systematic study with the population: factory workers. Intervention: night shift work. Comparation: morning and afternoon shift work. Outcome: hypertension and sleep patterns. The article search process was carried out according to the PRISM Flow Diagram and searched through several indexes such as PubMed, ScienceDirect, Google Schoolar, and Springer Link with the search keywords “Night Shift” AND “Hypertension” AND “Sleep” AND “Worker”. The articles used are articles from 2013-2022 and are written in English.Results: A total of 11 articles originating from the Asian continent (China, Indonesia, South Korea, Malaysia, and Japan) were considered suitable for meta-analysis. From the results of data analysis that has been carried out, it is known that factory workers who work night shifts have a risk of experiencing hypertension (aOR= 3.43; 95% CI= 2.48 to 4.72; p<0.001), and disturbed sleep patterns (aOR= 3.63; 95% CI= 2.66 to 4.95; p<0.001) compared with morning and afternoon shift workers and the results were statistically significant.Conclusion: Night shifts can increase the risk of hypertension and sleep disturbances in factory workers. Keywords: Night shift, hypertension, sleep pattern, factory worker Correspondence:Amanda Kesli Ramadhani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No.36, Kentingan, Jebres, Surakarta 57126, Central Java. Email. amandakesly@yahoo.com. Mobile: 085692832776.